A method of detecting online public opinions based on the query log of search engine. (1st January 2012) - Li, Zhihong; Zhu, Tao
Online public opinion has become a hot academic research in China, however, existing detecting approaches have some limitations. Based on literature studies, netizen are the crucial factor of guiding the direction of online public opinion, and the large amount of data shows that the information of online public opinion would have a crucial impact on netizens' search behaviour (using search engine). To this end, according to the group behaviour of netizens, this paper proposed a new detecting method of online public opinion based on query log of search engine, and described the specific steps. This method has a high feasibility and reliability, and provides a new idea for detecting online public opinion.